Design and Evaluation of a Novel Symmetric Multichannel Transmit/Receive Coil Array for Cardiac MRI in Pigs at 7 T - Elabyad, Ibrahim A.; Terekhov, M.; Stefanescu, Maria R.; Lohr, D.; Fischer, M.; Schreiber, Laura M. (IEEE transactions on microwave theory and techniques, 2019)
A dedicated, novel, multichannel transmit/receive (Tx/Rx) coil array was designed, simulated, and tested for cardiac magnetic resonance imaging (cMRI) of pigs at 7 T. The cardiac array was composed of 16 elements with physically independent anterior and posterior parts. The array was connected to the MRI scanner in the parallel transmit (pTx) mode forming an 8-channel transmit and 16-channel receive (8Tx/16Rx) coil configuration. The anterior array was composed of four central octagonal elements, which were decoupled using a common central ring (CCR) and shared decoupling capacitors. The surrounding four triangular elements were decoupled from the central four elements using gaps and capacitive decoupling. In total, the eight elements of the anterior array resembled a coil with a symmetrical circular shape. Due to the advantageous arrangement of the elements in conjunction with the novel decoupling method of a CCR, the coupling between the adjacent loop elements was minimized. The posterior array was built using a 4 × 2 standard rectangular, symmetric element configuration. The dedicated cardiac array was tested in phantom and in ex vivo MR measurements with a female pig of 46 kg. The dedicated coil array enhanced the signal-to-noise ratio (40 ± 27) in ex vivo measurements of the pig heart by about three times compared to a coil prototype for cardiac human imaging (11.8 ± 7). High-resolution, ex vivo cardiac images were acquired with an in-plane resolution of up to 0.3 mm ×0.3 mm using the dedicated pig coil array. The novel cardiac array supports parallel imaging with an acceleration factor (R) of 4 without increasing the mean g -factor within the heart region beyond 1.15.